Demonstration of the Rationale for Therapeutic Drug Monitoring of Isavuconazole: A Case Report with a Lung Transplant Recipient - Eliška Dvořáčková; Andrea Zajacová; Jan Havlín; Eva Klapková; Robert Lischke; Ondřej Slanař; Martin Šíma (Prague Medical Report, 2023)
Mucormycosis is a rare invasive fungal disease diagnosed in immunocompromised patients, including those with diabetes or iron overload, and in patients treated for hematological malignancies or after transplantation. Isavuconazole is a triazole antifungal effective against Mucorales with good tolerability, but with potential for relatively high interindividual variability in pharmacokinetics. This report demonstrates the case of a lung transplant recipient treated with isavuconasole that exhibits a very long elimination half-life of 159 hours, and discusses the practical implications of this finding for dosage adjustment and need for therapeutic drug monitoring.